First Report of Native Parasitoids of Fall Armyworm Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in Mozambique - Caniço, Albasini (Insects, 2020)
SIMPLE SUMMARY: In 2016, a highly destructive insect pest with origin in the Americas was detected in Africa. The pest is known to feed primarily on maize which is a staple food in the continent. Since then, farmers have been using chemical insecticides to control the pest. Chemical insecticides are expensive and harmful to the environment. In this article, the authors Albasini Caniço, António Mexia, and Luisa Santos discuss the possibility of application of an alternative method of control known to be environmentally friendly and economically sustainable in the long term. The method, known as “biological control”, can be easily implemented by farmers, and has the potential to reduce the population of the insect pest and production costs, and bring long term benefits to the environment. ABSTRACT: The alien invasive insect pest Spodoptera frugiperda Smith (Lepidoptera: Noctuidae), commonly referred to as fall armyworm (FAW), is causing significant losses to maize production in Africa since its detection in 2016. As an emergency response, governments in several countries distributed and/or promoted massive use of synthetic insecticides among smallholder farmers to fight FAW. The inappropriate use of synthetic insecticides by non-trained and ill-equipped farmers raises environmental and health concerns. This study aimed to assess the occurrence of native parasitoids of FAW, their parasitism rates, and relative abundance in the central province of Manica, Mozambique. A field collection of FAW egg masses and larvae was conducted from May to August 2019 (dry season of the 2018/2019 cropping season) and in December 2019 and January 2020 (rainy season of 2019/2020 cropping season). A total of 101 egg masses and 1444 larvae of FAW were collected from infested fields. Five larval parasitoids were recorded, but no egg parasitism was observed. Coccygidium luteum Brullé (Hymenoptera: Braconidae) and Drino quadrizonula Thomson (Diptera: Tachinidae) were the primary parasitoids. Maximum parasitism of 23.68% and 8.86% and relative abundance of 100 and 96.3 were recorded for C. luteum and D. quadrizonula, respectively. Total parasitism by different parasitoid species was at 9.49%. Cultural practices favoring the action of these parasitoids should be advocated.